ChemInform Abstract: Facile Synthesis of Spinel CuCr2O4 Nanoparticles and Studies of Their Photocatalytic Activity in Degradation of Some Selected Organic Dyes. Issue 45 (November 2015) - Paul, Bappi; Bhuyan, Bishal; Purkayastha, Debraj Dhar; Dhar, Siddhartha Sankar; Behera, Satyananda
Abstract Quasi‐spherical CuCr2O4 spinel nanoparticle catalysts (5‐35 nm) are prepared via urea assisted co‐precipitation from a stoichiometric aqueous solution of Cu(NO3)2 and Cr(NO3)3 (110 °C, 3 h) followed by calcination of the dried mixed hydroxide precipitate (1.